Public Perceptions of Synthetic Biology Solutions for Environmental Problems - Hobman, Elizabeth V.; Mankad, Aditi; Carter, Lucy (Frontiers in Environmental Science, 2022)
This study explored public attitudes towards developing synthetic biology solutions for environmental problems: 1) invasive pest management, 2) endangered species conservation, 3) bioremediation of waterways, and 4) coral reef restoration. A sample of 4,593 Australians were surveyed online. Results showed that public support for a synthetic biology solution was highest for the bioremediation of waterways using an engineered pseudo-organism. Genetically engineering endangered species, invasive pests and coral received comparatively less support than bioremediation, however, support was still moderate to high for these other applications. More proximal behavioural intentions were also rated moderately to more favourably. Our findings underscore the importance of engaging with those who are likely to be impacted by the synthetic biology solution if it were introduced. At this local level, we can then obtain a better understanding of how people are likely to respond to the synthetic biology solution, which can inform how the solution is developed, and when, where, and how it might be implemented in the future.